PERCEIVED CHALLENGES AND BENEFITS OF BUSINESS ENGLISH LEARNING: A CASE STUDY AT UNIVERSITAS CATUR INSAN CENDEKIA - Viar Dwi Kartika; Yuni Awalaturrohmah Solihah; Virga Putra Darma (Universitas Wiralodra, 2026)
This study focuses on how fourth-semester students in the Faculty of Economics and Business at UCIC perceive the English for Business course and its relevance to their academic and professional development. Employing a qualitative descriptive method supported by both closed-ended and open-ended survey responses, the research aims to explore students’ levels of understanding, the challenges they encounter, the benefits they experience, and their expectations for course improvement. Findings indicate that the qualitative analysis of 95 fourth-semester students revealed key challenges and benefits. Major difficulties included limited business vocabulary, insufficient practice, moderate confidence, speaking anxiety, and challenges in presentations, business writing, and role-plays. Despite these obstacles, students reported significant gains, such as improved speaking skills, preparedness for business contexts, enhanced communication, increased confidence, and application of skills in real-life situations. Students suggested curriculum improvements, emphasizing real-world practice, better vocabulary instruction, innovative learning media, career-focused topics, and interactive teaching methods. Students faced challenges including limited vocabulary, speaking anxiety, and insufficient practice. Despite this, they gained improved speaking skills, confidence, and professional readiness. This study highlights the importance of adaptive, needs-based pedagogy, task authenticity, and learner agency, offering actionable insights for ESP curriculum development